The aetiology and pathogenesis of tropical ulcer - Adriaans, Beverley (Division of Dermatology, 2017)
Tropical ulcer is a very specific form of cutaneous ulceration. It occurs worldwide in most tropical and a number of subtropical areas. The disease occurs mainly in older children and young adults with children under the age of 5 and adults over 45 years rarely being affected. Ulcers occur most commonly on the lower leg but may occur on the upper limb. Although most ulcers normally heal slowly over many weeks or months, some ulcers may recur. Recognised complications include squamous cell carcinoma, gangrene and osteitis, although these are rare. A number of authors have reported on the disease and suggested diet, trauma and infection as aetiological factors for this condition. This survey was thus conducted to assess as many of these factors as possible. The study took place in 5 tropical areas, namely Zambia, Gambia, southern India, Fiji and Papua New Guinea. Consultations took place at hospitals, rural clinics, health centres and villages. Although many authors have suggested that the disease is related to malnutrition, few have objectively assessed the nutritional status of the patients and compared it with controls. Those studies which included objective assessments were limited to small areas and only investigated specific parameters. In order to investigate the immune response of the host to an anaerobic infection, the antibody levels to the organisms isolated from the ulcers were measured by an ELISA test. The local host response to an infection with a Fusobacterium species was assessed by the number of antibody secreting B-lymphocytes at the site of the ulcers. These parameters may play a role in the localisation of the ulcers and account for recurrent infections.